CiLiQuant: Quantification of RNA Junction Reads Based on Their Circular or Linear Transcript Origin - Morlion, Annelien; Hulstaert, Eva; Vromman, Marieke; Anckaert, Jasper; Everaert, Celine; Vandesompele, Jo; Mestdagh, Pieter (Frontiers in Bioinformatics, 2022)
Distinguishing circular RNA reads from reads derived from the linear host transcript is a challenging task because of sequence overlap. We developed a computational approach, CiLiQuant, that determines the relative circular and linear abundance of transcripts and gene loci using back-splice and unambiguous forward-splice junction reads generated by existing mapping and circular RNA discovery tools.